A Ground-Up Model for Gun Violence Reduction: A Community-Based Public Health Approach. Issue 1 (2nd January 2016) - Byrdsong, T. Rashad; Devan, Angela; Yamatani, Hide
Abstract : The suggested strategy for the reduction of violence is to collaboratively address the problem, based on an intervention system focused on prevention, rehabilitation, and development. This strategy is capable of engaging community residents in positive ways, and it empowers them to take ownership and sustain much-needed resident commitments to achieve long-term public safety. The community residents largely insist that over-reliance on law enforcement to control violence invites further affliction among Black youth and adults.